2020
DOI: 10.1192/bjo.2020.48
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ and psychiatrists’ attitudes towards antidepressant withdrawal

Abstract: Background There has been a recent rise in antidepressant prescriptions. After the episode for which it was prescribed, the patient should ideally be supported in withdrawing the medication. There is increasing evidence for withdrawal symptoms (sometimes called discontinuation symptoms) occurring on ceasing treatment, sometimes having severe or prolonged effects. Aims To identify and compare current knowledge, attitudes and practices of general practitioners (GPs) and psychiatrists in Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The subtheme of self‐managed withdrawal with limited resources aligns with other research, with one prior survey study ( n = 342) identifying subthemes related to insufficient information and support 9 . Research also indicates a discrepancy between healthcare professionals’ claims that patients are informed about withdrawal symptoms and patient reports 38 . This was evident in a recent large online survey ( n > 1000) which revealed that less than 5% of patients reported being told anything about antidepressant withdrawal effects by their prescribers 39 .…”
Section: Discussionsupporting
confidence: 67%
“…The subtheme of self‐managed withdrawal with limited resources aligns with other research, with one prior survey study ( n = 342) identifying subthemes related to insufficient information and support 9 . Research also indicates a discrepancy between healthcare professionals’ claims that patients are informed about withdrawal symptoms and patient reports 38 . This was evident in a recent large online survey ( n > 1000) which revealed that less than 5% of patients reported being told anything about antidepressant withdrawal effects by their prescribers 39 .…”
Section: Discussionsupporting
confidence: 67%
“…Further, symptoms may not occur for weeks. The ambiguity may reinforce the tendency to not inquire about co-occurring physiological withdrawal symptoms (as well as reinforcing the belief that these syndromes are rare), 47,80,81 but timing tells the tale 3,56,82 : any dosage decrease may trigger any type of withdrawal symptom, even if reported weeks later. 4,16,83 In light of their tendency to emerge after dosage reductions, 82 it is not difficult to distinguish withdrawal symptoms from relapse.…”
Section: The Significance Of Withdrawal Symptomsmentioning
confidence: 99%
“…Conversely, other studies suggest a relatively stable prevalence of mental disorders or under-recognition and undertreatment 20 21. Other facilitating factors possibly contributing to the rise in antidepressant prescriptions and use are the availability of new medications with a better risk–benefit profile (e.g., selective serotonin reuptake inhibitors (SSRIs)),22 the introduction of generics on the market,23 experience or fear of withdrawal symptoms,24 other socioeconomic and cultural factors (e.g, stigma mental health well-being campaigns)25 26 or increased duration of treatment 27 28…”
Section: Introductionmentioning
confidence: 99%